Vitamin D Receptor Inhibits NLRP3 Activation by Impeding Its BRCC3-Mediated Deubiquitination - Rao, Zebing; Chen, Xin; Wu, Junxian; Xiao, Mengjun; Zhang, Jing; Wang, Binghao; Fang, Lei; Zhang, Hongjie; Wang, Xiaoming; Yang, Shuo; Chen, Yunzi (Frontiers in Immunology, 2019)
Abstract The NLRP3 inflammasome is a multiprotein oligomer responsible for activation of the inflammatory response by promoting the maturation and secretion of the pro-inflammatory cytokines IL-1β and IL-18. Dysregulation of this inflammasome has been linked to several autoimmune diseases, indicating that NLRP3 is tightly regulated to prevent aberrant activation. The regulation of NLRP3 activation remains unclear. Here, we report the identification of vitamin D receptor (VDR) as a negative regulator of NLRP3 oligomerization and activation. VDR can physically bind NLRP3 and block the association of NLRP3 with BRCC3. When BRCC3-mediated deubiquitination of NLRP3 is inhibited by VDR, NLRP3 activation is subsequently inhibited. In the absence of VDR, caspase-1 activation and IL-1β release are increased in response to LPS-induced inflammation or alum-induced peritoneal inflammation, indicating that VDR is a negative regulator of NLRP3 inflammasome activation in vivo. In addition, vitamin D negatively regulates the NLRP3 inflammasome via VDR signalling to effectively inhibit IL-1β secretion. These studies demonstrate that VDR signalling constrains NLRP3 inflammasome activation and might be a potential treatment target for NLRP3 inflammasome-related diseases.